Therapeutic effect and mechanism of gigantol on hyperuricemia - Yuanfan Wu; Xia Sun; Yuhan Jia; Tianshu Gao; Jin Xu; Youqiao Qian; Naiqi Pei; Lilin Wang; Qiaohong Zheng; Honglei Li; Zhen Chen; Yijiao Liu; et al. (Frontiers in Endocrinology)
This study aimed to evaluate the therapeutic effects of gigantol on hyperuricemia (HUA) and investigate the underlying mechanism of HUA. A mouse model of HUA was made by gavage of potassium oxonate, and HK-2 and AML12 cell models were made by adenosine and xanthine oxidase (XOD) induction. We tested the levels of uric acid (UA), creatinine (CRE), blood urea nitrogen (BUN), cellular UA, and XOD activity. The levels of NOD-like receptor thermal protein domain 3 (NLRP3) and other inflammatory factors were detected by enzyme-linked immunosorbent assay (ELISA) kits. XOD is a protein related to the NLRP3 pathway and also serves as an UA transporter. We found that the levels of UA, CRE, and BUN increased in serum but decreased in urine in HUA model mice. After gigantol treatment, UA, CRE, and BUN levels in serum decreased, whereas their levels in urine increased. The levels of NLRP3 and interleukin-1β (IL-1β) were lower and the expression of NLRP3-related protein decreased after gigantol treatment. In conclusion, gigantol exhibits a therapeutic effect on HUA, and the mechanism may be related to inhibiting XOD activity to reduce UA production, regulating the expression of UA transporters to increase UA excretion, and inhibiting the activation of NLRP3 inflammatory signaling.